In Critical Condition: (Un)Becoming Bodies in Archival Acts of Truth Telling - Lee, Jamie A. (Archivaria, 2019)
This article engages the archives as a space of multimodal truth telling that challenges the traditional understanding of archives as “authorized evidence.” This inquiry, specifically into oral history interviews produced for and within the archives, works to further disrupt the long-standing traditional archival paradigm that advocates for a static and fixed archival record. To recognize an archival record that is neither static nor singular is to recognize how static and singular records have functioned in the archives. Drawing on Michel Foucault’s 1983 essays and lectures on parrhesia – often translated in English as “free speech” and defined as the process of telling and confronting one’s truth – I posit that multiplicities related to subjects and subjectivities offer kaleidoscopic connections between the storyteller and the stories and truths they tell. Through analysis of distinct oral history interviews I conducted for the Arizona Queer Archives and with an emphasis on the narrator, Foucault’s parrhesiastes, I argue that truth telling emerges through oral history methods that might best support (un)becoming bodies and bodies of knowledge in the archives to trouble the archival record in a generative way. RÉSUMÉ Cet article pose les archives comme espace de récit de vérité multimodal, remettant en question la conception traditionnelle des archives comme « preuve autorisée ». Cette recherche, particulièrement par des entrevues d’histoire orale effectuées par et dans les archives, vise à ébranler encore davantage le vieux paradigme archivistique traditionnel prônant un document d’archive figé et défini. De reconnaitre un document d’archive qui n’est ni statique ni unique implique également de reconnaitre la façon dont les documents statiques et uniques ont fonctionné dans les archives. Puisant dans les essais et lectures de Michel Foucault de 1983 sur la parrêsia – souvent traduite en français comme le « franc-parler » et définie comme étant le processus par lequel on énonce une vérité tout en la confrontant – j’avance que les multiplicités liées aux sujets et aux subjectivités offrent des liens kaléidoscopiques entre le narrateur et l’histoire et les vérités exprimées. Par l’analyse d’entrevues d’histoire orale spécifiques que j’ai menées pour les Arizona Queer Archives, et avec un accent mis sur le narrateur, le parrèsiaste de Foucault, je soutiens que l’expression de la vérité émerge des méthodes d’histoire orale qui pourraient être les plus à même de porter des corpus en (non)devenir et des corpus de connaissances dans les archives qui ébranlent les archives de façon productive.